15 Structured Geriatric Liaison Services in Mental Health Inpatient Facilities. (6th February 2020) - Babu, B; Khalid, A; Sadiq, S; Essem, J; Ruiz-Mendoza, E
Abstract: Introduction: Older people admitted to mental health facilities may be at increased risk of deterioration in the physical co-morbidities and increased rates of mortality when admitted in acute medical settings. Our model of care focuses on intervening in the physical aspect of patients admitted in the mental health unit addressing their comorbidities and polypharmacy and offering staff support during the admission process. Our Older Mental Health Unit is based in the district hospital with a total of 22 beds for people over 65 years old distributed in two areas: dementia with behavioral and psychological symptoms (BPS) and functional disorders. Methods: Allocated geriatrician once a week to attend MDT and medical ward rounds. 5 working days telephone consultations for advice and supporting trainees in teaching and research. We measure the impact of our intervention comparing the data predating our intervention comparing 20 patients in each period 2016 and 2018. Results: Mean age increased from 74.3 to 77.8 in a two year period with an average of 3.5 medical co-morbidities. Reduction in polypharmacy from 7.15 to 5.5 number of medication, 58% reduction in the number of hospital transfers and 90% reduction in specialty referrals. Conclusions: Structured Geriatric Liaison Services in Mental Health in inpatient facilities are shown to be effective in reducing acute hospital and outpatient clinic attendances minimising the challenges of management of these patients in non-mental health facilities.